Detection of peanut (Arachis hypogaea) allergens in processed foods by immunoassay: Influence of selected target protein and ELISA format applied. (August 2015) - Montserrat, M.; Sanz, D.; Juan, T.; Herrero, A.; Sánchez, L.; Calvo, M.; Pérez, María D.
Abstract: Direct competitive and sandwich ELISA formats developed to determine Ara h1 and Ara h2 proteins were applied in the detection of peanut in model biscuits prepared with a commercial peanut butter as ingredient. The sandwich format for Ara h2 protein could detect the addition of 2.5% peanut butter, whereas the same format for Ara h1 could not detect 5% added peanut. Direct competitive formats for Ara h1 and Ara h2 proteins could detect the addition of 1% and 0.05% peanut butter, respectively. Therefore, competitive format for Ara h2 was selected to be evaluated by four laboratories, obtaining adequate results in term of repeatability and reproducibility. Results obtained indicate that processing decreased the level of extracted proteins and underestimated the amount of Ara h1 and Ara h2 proteins, the effect being more severe for Ara h1. The selection of the target protein and the ELISA format applied greatly influence the detection of peanut in processed foods. Highlights: Sandwich and competitive ELISAs for Ara h1 and Ara 2 were developed to detect peanut. Competitive format showed greater sensitivity than sandwich format for both proteins. Competitive format for Ara h2 showed the greatest sensitivity to detect added peanut. The selected target protein and ELISA format influence detection of peanut in foods. The interlaboratory study of competitive ELISA for Ara h2 gave reproducible results.